Exploring Islamic Marketing Strategies Among Gen Z Entrepreneurs Using Social Media: A Case Study From STIE Balikpapan - Susila, Haryadi Jaka (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
The increasing involvement of Generation Z university students in social media-based entrepreneurship reflects digital adaptation and ethical dilemmas regarding Islamic business conduct. This study explores how Gen Z student entrepreneurs from STIE Balikpapan apply Islamic marketing strategies while utilizing platforms like Instagram, WhatsApp, and TikTok. Employing a qualitative case study method, data were collected through in-depth interviews with 16 active student entrepreneurs and document analysis of their digital marketing practices. The findings show a meaningful integration of Islamic values such as honesty, transparency, fairness, and trustworthiness into their promotional activities. However, challenges remain in consistently applying Islamic ethics under market competition, limited Sharia knowledge, and evolving consumer expectations. This study contributes to the literature on ethical marketing and provides insight into how young Muslim entrepreneurs can align digital business strategies with Islamic principles.